Reconstruction of Domestic Marine Fisheries Catches for Oman (1950-2015) - Khalfallah, Myriam; Zylich, Kyrstn; Zeller, Dirk; Pauly, Daniel (Frontiers in Marine Science, 2016)
Domestic marine fisheries in Oman are increasingly viewed as the eventual economic alternative to the soon to be depleted oil reserves. This has galvanized the Omani government to invest in the management of its marine living resources. This study aims to provide a better estimation of Oman's domestic marine fisheries catches that can be used to improve fisheries management in the country. Using the catch reconstruction approach, total domestic marine fisheries catches by Oman are estimated for the time period 1950-2015, including reported and previously unreported large-scale and small-scale commercial catches, subsistence, and recreational catches, as well as major discards. Catches from the Omani exclave, Musandam, are estimated separately, given this governorate’s geographical separation from the rest of Oman. Reconstructed total catches increased from around 64,000 t∙year-1 in the 1950s to over 200,000 t·year-1 in the 2000s, which are overall 1.2 times the landings reported by the FAO on behalf of Oman. Fish stocks need to be sustainably managed to allow long-term economic viability. This cannot be done without the improvement of fisheries statistical systems around the world, including in Oman.